5r+-9=-7r+6

Simple and best practice solution for 5r+-9=-7r+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5r+-9=-7r+6 equation:


Simplifying
5r + -9 = -7r + 6

Reorder the terms:
-9 + 5r = -7r + 6

Reorder the terms:
-9 + 5r = 6 + -7r

Solving
-9 + 5r = 6 + -7r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '7r' to each side of the equation.
-9 + 5r + 7r = 6 + -7r + 7r

Combine like terms: 5r + 7r = 12r
-9 + 12r = 6 + -7r + 7r

Combine like terms: -7r + 7r = 0
-9 + 12r = 6 + 0
-9 + 12r = 6

Add '9' to each side of the equation.
-9 + 9 + 12r = 6 + 9

Combine like terms: -9 + 9 = 0
0 + 12r = 6 + 9
12r = 6 + 9

Combine like terms: 6 + 9 = 15
12r = 15

Divide each side by '12'.
r = 1.25

Simplifying
r = 1.25

See similar equations:

| -1(3x+1)=-7 | | 4(2x+b)-3(4-3c)=5b+6x | | (2x-3)/(-1)=(1-4x)/2 | | 27y-18= | | 5r^2-22r+21=0 | | 2x-1/21=x-5/24 | | 5n+5=2p | | 50=3x+5x | | 180=2(4y-15)+7 | | 7(t-8)+50=10t+14+2t | | 8n-6+1n+10= | | .1(40x)-1/2(16) | | 3(x-7)+2x=10 | | 3(x+2)=0.55(2x+3) | | 180x(2x+8)= | | X+.05=2.10 | | (-3g)-(-1)= | | 4u+9=69 | | 5q+14=72q | | 2q+375=857 | | 3(x+13)=7x-9 | | 7(t-8)+50=10t+15+2t | | 8e-(-2)=6 | | 4/9x^2=3 | | y-1/3=1/6 | | 9+5r+5r+2r= | | 30=1x-80 | | -1.4-2.7= | | 9(2x+3y)= | | 174=14.3*c*27 | | 4x-8=3y-15 | | 8h+20=69 |

Equations solver categories